Percutaneous endovascular removal of intracardiac migrated port A catheter in a child with acute lymphoblastic leukemia - Cakir,Feraye (2014)
A 2-year-old boy with acute lymphoblastic leukemia was presented with peripherally inserted central catheter dysfunction. Radiological examinations revealed a catheter remnant in the right atrium extending into pulmonary vein. The catheter remnant was successfully removed from the right atrium by percutaneous endovascular intervention without any complications.